Unlocking the M13 (f1 and fd) virion : investigation into the role of the pIII C-domain of F specific filamentous bacteriophage in infection : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, Palmerston North, New Zealand. - Bennett, Nicholas James (Massey University, 2009)
Ff filamentous bacteriophage infect male (F+) strains of Escherichia coli and are assembled at the cell membranes, by a secretion-like, non-lethal process. The pIII protein, located at one end of the virion-filament, is required at both the beginning and the end of the phage life cycle. During infection, the N-terminal domains of pIII, N2 and N1, bind to the primary and secondary host receptors, F pilus and TolA protein, respectively. At the end of the life cycle, the pIII C-domain mediates the termination and release of virions. Thus, both entry and release involve structural transitions of the virus coupled to membrane transactions of the virion proteins. "Unlocking” of the highly stable virion presumably results in membrane integration during entry, whereas a reverse event, “locking” of the virion, occurs upon detachment from the membrane at termination step of assembly/secretion. Recently, it was shown that the pIII C-domain plays an active role at the step of entry. This finding implicates the C-domain of pIII in “unlocking” of the virion, presumably resulting in the exposure of the membrane anchor at the very C-terminus of pIII (Bennett & Rakonjac, 2006). To further this work, this thesis has mapped the portion of the pIII C-domain required for infection, by constructing a set of nested deletions of the C-domain fused to the receptor binding domains N1 and N2, and then determined the infectivity of phage carrying the mutant proteins. This mapped the portion of the C-domain required for phage infection is different to that required for termination of assembly. The different requirement for entry and release suggests that the two processes are carried out by distinct mechanisms and/or depend on different sets of accessory proteins. In addition, a system was designed for the efficient production and purification of very short virions, the length of which is 1/20 that of the wild-type f1. These short virions, called microphage, are the first step towards the structural analyses of the phage termini cap structures, of which one contains pIII in the “locked” conformation.
Keywords: Filamentous bacteriophage; Microphage production system; Fields of Research::270000 Biological Sciences::270100 Biochemistry and Cell Biology